Radical social work in practice : making a difference - Ferguson, Iain, 1954-; Woodward, Rona.; British Association of Social Workers (Bristol, UK ; Portland, OR : Policy Press, 2009)
This book promotes a practice that is rooted in a commitment to positive change and to social justice that will offer a breath of fresh air to students and practitioners alike.
Social work in a divided society -- The radical kernel -- Neoliberalism and social work -- State social work: constraints and possibilities -- The 'third sector': a radical alternative? -- Beyond good intentions: the challenge from service users and carers -- Rediscovering collective approaches -- Conclusion: social work - a profession worth fighting for.
"BASW." -- t.p.
Includes bibliographical references (p.165-183) and index.
Keywords: Social service -- Great Britain